Explaining Iranian midwives' experiences of providing healthcare services during the COVID-19 pandemic: a qualitative study - Sedigheh Moghasemi; Elham Adib Moghaddam; Sahar Arab (BMC, 2023)
Abstract Background COVID-19 has changed and challenged the way health and maternity care is provided. Midwives are among the first and most influential maternity care providers during the COVID-19 pandemic; however, there is inadequate information about their experiences in providing healthcare services, particularly in Iran. The present study was conducted to explain the midwives' experiences of providing healthcare services during the COVID-19 pandemic in Gorgan. Methods The present study was conducted qualitatively through the inductive content analysis method in 2022. Data were collected through semi-structured interviews. A total of 21 individuals were selected as participants using a purposeful method and the maximum diversity strategy. Results Data analysis led to the emergence of 377 codes, 12 subcategories, and 3 main categories, including, the laborious occupational challenges for midwives during the pandemic, identifying and creating new opportunities for the development of the midwifery profession, and the lack of perceived organizational and social support. Conclusions During the COVID-19 pandemic, midwives experienced various challenges in providing healthcare services, yet sacrificed themselves to perform their duties and provide quality care incessantly. The COVID-19 pandemic was a combination of laborious occupational challenges and individual and professional growth opportunities for midwives in Iran. Strong and managed organizational support is essential to overcome the crisis, maintain the workforce, and empower them to deal with future crises.